Effect of Alcohol-Patterns in the Resiliency of South Korean Firefighters from Job Stress and Incident Impact - Cha, Jingyung; Park, Chanseok; Bang, Seonghwan; Cho, Byungjun (International Journal of Engineering and Technology, 2019)
In The purpose of this study is to improve the safety and work efficiency of firefighters by exploring how resilience contributes to the relationship and to provide basic data for the management program of traumatic stress. With the help of the fire department, we collected data through a self - report questionnaire consisting of self - report scale for 300 public officials. Data collection methods were based on e-mail sending and returning methods, There were 270 subjects in the analysis except for 30 subjects who were not or not reliable.Normal drinking group showed mediating effect of resiliency(p
Keywords: Firefighter; Patterns of alcohol use; Incident Impact; Job stress; Resilience